Impact assessment of water scarcity at Somntongo in the lowveld region of Swaziland (2008)
A survey was conducted to assess the impact of water scarcity in Somntongo, in the lowveld region of Swaziland. The study adopted the use of questionnaire, interview schedules and focused group discussions. Information sought included sources of water, distances between water sources and places of residence, and the effect of water scarcity on the various aspects of human activities. The study revealed that only two rivers and five boreholes were the major sources of water while distances of as much as 5 - 20 km were covered in search of water. In about 82% of the homesteads, the water use was about 3.3 litres/head/day and 2.3 litres/livestock/day. These are quite low compared to the minimum standards of 25 litres/head/day, and between 25 and 35 litres/livestock/day. Water scarcity has resulted in the death of livestocks; some cultivated crops have withered while others are not cultivated for lack of irrigation water. In some instances, schools have temporarily been closed due to water shortages. Construction of more boreholes and dams can reduce the water scarcity and promote the standard of living in the community.